2010
DOI: 10.1016/j.econlet.2010.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Is the wage curve formal or informal? Evidence for Colombia

Abstract: Abstract:The objective of this paper is to analyse the existence or not of a wage curve in Colombia, paying special attention to the differences between formal and informal workers, an issue that has been systematically ignored in the wage curve literature.The obtained results using microdata from the Colombian Continuous Household Survey (CHS) between 2002 and 2006 show the existence of a wage curve with a negative slope for the Colombian economy. Using information on metropolitan areas, the estimates of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 8 publications
1
17
1
Order By: Relevance
“…Following Maloney (), Jutting and De Laiglesia () and Ramos et al. (), we define formal workers as those who are registered with the social security administration. During the sample period that we investigate, approximately 28 per cent of wage earners in Turkey did not have the protection of the mandatory social security system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following Maloney (), Jutting and De Laiglesia () and Ramos et al. (), we define formal workers as those who are registered with the social security administration. During the sample period that we investigate, approximately 28 per cent of wage earners in Turkey did not have the protection of the mandatory social security system.…”
Section: Introductionmentioning
confidence: 99%
“…See Berg and Contreras () for an estimation of the informal wage curve for Chile, and Ramos et al. () for Colombia.…”
mentioning
confidence: 99%
“…After excluding the selfemployed or paid family workers, the unemployed, inactive and missing observations, we are left with over 739,490 observations. The literature on the wage curve in other South American countries is rather limited and include papers on Argentina (Galiani, 1999), Chile (Berg and Contreras, 2004;Garcia and Granados, 2005), Colombia (Arango et al, 2010;Ramos et al, 2009) and Uruguay (Bucheli and González, 2012). Almost all of these studies rely on microdata and report unemployment elasticities around -0.1.…”
Section: Introductionmentioning
confidence: 99%
“…() found a wage curve for all workers, although when the information was broken down between formal and informal workers, Ramos et al . (, p.6) found that ‘only wages of informal workers react to local labour market conditions’; however, the wages of formal workers, who are the focus of our paper, do not. The replies to the survey indicate that the wages of new hires for all occupational groups are based on a predefined internal wage structure.…”
Section: Introductionmentioning
confidence: 99%